2017
DOI: 10.1161/strokeaha.117.018187
|View full text |Cite
|
Sign up to set email alerts
|

Confounding by Pre-Morbid Functional Status in Studies of Apparent Sex Differences in Severity and Outcome of Stroke

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 34 publications
(26 reference statements)
7
39
2
Order By: Relevance
“…Women’s all-cause mortality after stroke has been put forward as lower when adjusting for other relevant factors [ 18 ], but there are also results opposing that [ 19 ] as well as dismissing any significant differences [ 20 ]. Variations in the findings on sex differences between previous studies [ 21 25 ] may not only reflect differences in the population but also differences in the adjustments performed. Such general differences in statistical approach have also been pointed out in recently published American guidelines [ 14 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Women’s all-cause mortality after stroke has been put forward as lower when adjusting for other relevant factors [ 18 ], but there are also results opposing that [ 19 ] as well as dismissing any significant differences [ 20 ]. Variations in the findings on sex differences between previous studies [ 21 25 ] may not only reflect differences in the population but also differences in the adjustments performed. Such general differences in statistical approach have also been pointed out in recently published American guidelines [ 14 ].…”
Section: Discussionmentioning
confidence: 90%
“…We found the rates of good 1-year functioning after IS to be lower in women, in line with previous studies [ 21 23 ]. There are also studies pointing to no significant differences [ 24 , 25 ]. Any such differences could be attributable to sex bias in the diagnosis and treatment or to the biological differences in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of activity limitations demonstrated that prestroke function was an important contributor to the sex difference in this outcome. 15,18 Although many authors considered prestroke function or cardiovascular comorbidities as confounders, few considered musculoskeletal (eg, osteoporosis or arthritis) or mental disorders that are more prevalent in women compared with men. 60 Associated with prestroke health is women's older age than men at the time of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][22][23][24] Common covariates included age, stroke severity, and comorbidities. There were 6 comparisons rendered nonsignificant by adjustment for covariates, 15,16,20,21,25 which were most commonly age, stroke severity, comorbidities, and health behaviors. Adjustment for covariates reduced the sex differences by between 2% and 47%.…”
mentioning
confidence: 99%
See 1 more Smart Citation